INNOVATIVE AND INFORMATION TECHNOLOGIES FOR DEVELOPING ASSOCIATIVE THINKING IN PRIMARY SCHOOL STUDENTS - Ortiqova, Zulfiya (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
In the context of rapid educational digitalization and evolving learning paradigms, developing primary school students’ associative thinking has become a strategic priority in modern pedagogy. Associative thinking allows learners to form meaningful connections between concepts, experiences, and cognitive structures, facilitating deep understanding and creative knowledge construction. This article examines the theoretical foundations and pedagogical significance of innovative technologies aimed at enhancing associative thinking in educational contexts. Through a qualitative analytical review of international and national scholarly literature, the study explores the cognitive nature of associative thinking, its role in creativity and divergent thinking, and its integration into modern instructional models. Special attention is given to digital concept mapping, problem-based learning, design thinking, gamification, and interactive multimedia tools as strategies to stimulate associative processes. Findings indicate that innovative technologies enhance cognitive flexibility, foster originality, and strengthen knowledge transfer by encouraging students to establish complex associative networks. The article concludes that systematic integration of technology-enhanced, learner-centered methodologies significantly contributes to the development of associative thinking and prepares students for adaptive and innovative performance in dynamic learning environments.